CYBERBULLYING AND CYBERSTALKING: BELONGINGS AND ANTICIPATION MEASURES IN INDIA - Rachna; Varshney, Rahul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the pervasive issue of cyberbullying and cyberstalking in India, analysing its detrimental effects on individuals and society. The abstract offers a brief overview of the paper's content, highlighting the importance of understanding and addressing these digital forms of harassment. The study also emphasizes the significance of implementing effective prevention measures to mitigate the escalating risks associated with online abuse. The rapid advancement of digital technology and the widespread use of social media platforms have given rise to various forms of cybercrimes, with cyberbullying and cyberstalking emerging as significant concerns in India. Cyberbullying encompasses repeated online harassment, threats, and defamation, whereas cyberstalking involves persistent digital surveillance and intimidation. Both forms of online abuse pose severe psychological, social, and legal challenges for individuals, particularly women, children, and marginalized groups. This study delves into the prevalence, impact, and legal frameworks associated with cyberbullying and cyberstalking in India. Through a mixed-method approach, including qualitative case studies and quantitative statistical analysis, this research explores the experiences of victims, the modus operandi of perpetrators, and the effectiveness of existing legal and policy measures. Despite various provisions under the Information Technology Act, 2000, and the Indian Penal Code, the study identifies significant gaps in enforcement, victim protection, and public awareness. The research highlights the psychological and societal repercussions of online harassment, leading to emotional distress, reputational damage, and, in extreme cases, self-harm or suicide. The study further investigates the role of law enforcement agencies, digital literacy initiatives, and intervention strategies in mitigating the menace of cyberbullying and cyberstalking. A comparative analysis with global best practices provides insights into how India can enhance its legal and technological frameworks to address these cyber threats more effectively. The research proposes recommendations such as stringent policy reforms, enhanced cybersecurity measures, AI-driven content monitoring, and the need for victim support mechanisms, including counseling and legal aid. The findings of this study will contribute significantly to academic literature, policy formulation, and public discourse, fostering a safer digital environment in India. By bridging the gap between legislation and practical enforcement, this research aspires to inform policymakers, law enforcement authorities, educators, and digital users about preventive and remedial measures, ultimately ensuring a robust cyberspace where individuals can exercise their rights without fear of online harassment.